Un supplementum al supplementum: Iscrizioni imperiali di Roma dagli anni ’90 a oggi - Orlandi , Silvia (Studia Europaea Gnesnensia, 2017)
In this survey article are collected and discussed most of the imperial inscriptions found in Rome after the pubblication of the last Supplement to CIL, VI by Géza Alföldy in 1996, together with a large number of possible corrections of the already published texts. The contributions are organized according the following schema: Addenda et corrigenda: small corrections, accidental gaps, methodological inconsistencies, texts to be removed. New texts and new studies: new discoveries (including new fragments of old inscriptions), both in archaeological excavations and in archives and repositories, just published (as imperial inscriptions or not) or still unpublished.